Management of neck dissection complications in head and neck cancers - Bhushan, Suhas N.; H. N., Arun (International Surgery Journal, 2019)
Background: Neck dissection is a vital step in eradicating the regional lymph node metastasis. The aim of study is to establish the incidence of post-operative complications in patients undergoing neck dissection and its management. Methods: A cross-sectional retrospective study of 82 patients admitted in the department of general surgery, BMCRI from June 2016 till January 2018 who underwent neck dissections for various head and neck cancers. These patients were studied for post-operative complications and their management. Results: Intra-operative complication being vascular injury (IJV repaired-2 cases), nerve injury and lymphatic injury (thoracic duct identified and serial ligation in 3 cases and right-side lymphatic duct injury in l case). Immediate post-operative complication being hemorrhage among 2 cases, re-opened in 1 case and managed by compression dressing in 1 case. Delayed complications being nerve injury among which marginal mandibular nerve injured in 5 cases, phrenic nerve in 1 case, vagus nerve in 1 case, spinal accessory nerve in 13 cases (palsy in 3 cases and praxia in 10 cases). Another delayed complication being chylorrhoea in 2 cases which was managed conservatively. Wound dehiscence noted among 4 cases, 2 of them were major (1 required redo flap, 1 managed conservatively) and 2 of them were minor complications. Conclusions: In our study, there were no peri-operative deaths. Nerves were most common structures injured. A careful pre-operative assessment, meticulous surgical technique, high quality post-operative care and appropriate rehabilitation help in preventing and managing complications.